Prespectives of Social Interactions Between Islamic Boarding School and Rural Community - Fedriana Oktaviani; Nurhadi Nurhadi; Saifuddin Zuhri (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This study aimed to examine the interaction between residents of an Islamic boarding school and the Tlepok village community and the community's perceptions of this interaction. The research utilized direct observation and interviews with community members who had interacted with the boarding school residents. Thematic analysis techniques were used to analyze the data, focusing on understanding the data, compiling codes, and identifying themes aligned with the research objectives. The study found that the interaction between the community and the Islamic boarding school residents has been positive. The boarding school residents displayed a polite attitude and respect toward the community, resulting in increased acceptance of the school's presence. The community has also benefited from the cooperative relationship with the boarding school, which has added to the trust and respect for the institution. The researcher used Max Weber's theory of social action, precisely the instrumental rationality action type, to explain this intertwined interaction phenomenon. This research highlights the importance of positive interaction and collaboration between Islamic boarding schools and the surrounding community. Building trust and mutual benefit can increase acceptance and a positive image for Islamic boarding schools. Penelitian ini bertujuan untuk mengkaji interaksi antara warga pondok pesantren dengan masyarakat dusun Tlepok serta persepsi masyarakat terhadap interaksi tersebut. Penelitian ini menggunakan pengamatan langsung dan wawancara dengan anggota masyarakat yang pernah berinteraksi dengan warga pesantren. Teknik analisis tematik digunakan untuk menganalisis data, berfokus pada pemahaman data, menyusun kode, dan mengidentifikasi tema yang selaras dengan tujuan penelitian. Studi ini menemukan bahwa interaksi antara komunitas dan warga pesantren telah positif. Warga pesantren menunjukkan sikap sopan dan hormat terhadap masyarakat, sehingga penerimaan terhadap kehadiran pondok pesantren meningkat. Masyarakat juga diuntungkan dengan adanya hubungan kerjasama dengan pondok pesantren yang menambah kepercayaan dan respek terhadap lembaga tersebut. Peneliti menggunakan teori tindakan sosial Max Weber, tepatnya tipe tindakan rasionalitas instrumental, untuk menjelaskan fenomena interaksi yang saling terkait ini. Penelitian ini menyoroti pentingnya interaksi dan kerjasama positif antara pondok pesantren dengan masyarakat sekitar. Hal ini juga menunjukkan bahwa membangun kepercayaan dan saling menguntungkan dapat menyebabkan peningkatan penerimaan dan citra positif bagi pesantren.